Peran Ganda Perempuan dan Problematikanya dalam Mendidik Anak (Studi terhadap Ibu yang Bekerja di Perkebunan PTPN XII Sempol, Kabupaten Bondowoso): The Dual Role of Women and Its Challenges in Child Education (A Study of Working Mothers at PTPN XII Sempol Plantation, Bondowoso Regency) - St. Mislikhah (Fenomena, 2010)
Within the development of an equal-partnership perspective based on a gender approach in various aspects of life, women's roles have undergone rapid changes. However, it is important to note that this development has not altered their traditional roles in the domestic sphere (reproductive roles). As a result, women's workload appears excessive. Working while fulfilling the role of a housewife is like a double-edged sword. Both roles cannot be neglected and require care and dedication. With the limited time available to women, problems arise in carrying out these duties, whether domestic tasks or child-rearing responsibilities. Dalam perkembangan pandangan kemitraan setara berdasarkan pendekatan gender di berbagai aspek kehidupan, peran perempuan mengalami perubahan yang pesat. Namun, perlu diperhatikan bahwa perkembangan ini tidak mengubah peran lama perempuan di lingkungan domestik (peran reproduktif). Oleh karena itu, beban kerja perempuan terkesan berlebihan. Bekerja dan menjalankan peran sebagai ibu rumah tangga ibarat pisau bermata dua. Keduanya tidak dapat diabaikan dan membutuhkan perhatian serta kesungguhan. Dengan keterbatasan waktu yang dimiliki perempuan, muncul berbagai masalah dalam menjalankan tugas-tugas tersebut, baik tugas domestik maupun tugas mendidik anak.